Probing the Timing Recruitment of Broca’s Area in Speech Production for Mandarin Chinese: A TMS Study - Zhang, Qian; Yu, Banglei; Zhang, Junjun; Jin, Zhenlan; Li, Ling (Frontiers in Human Neuroscience, 2018)
Although Broca’s area is widely recognized to play an important role in speech production, neuroscientists still debate on its timing recruitment across different languages. In order to investigate the precise time course of phonological encoding for Mandarin Chinese, we applied real repetitive transcranial magnetic stimulation (rTMS) and sham TMS within Broca’s area at five different time windows respectively (150 ms, 225 ms, 300 ms, 400 ms, and 500 ms) in picture naming task in Mandarin Chinese. To exclude unspecific TMS effects and to make sure that the effects observed in the study were really due to stimulation at Broca's area, we also conducted a control experiment with TMS stimulation at Vertex by a different group of subjects. Significant increases in RTs were observed when real TMS stimulation at Broca’s area was applied at 225 ms, 300 ms and 400 ms time windows with a peak at 225 ms, compared with sham TMS stimulation at other time windows. Our findings support the hypothesis that the phonological encoding in speech production for Chinese language may approximately start from 200 ms and end around 400 ms post target onset，a little earlier than that from 355 ms to 455 ms for Indo-European languages.